Implementasi Metode Design Thinking Dalam Perancangan Website Usaha Tanaman Potme Farm (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Technology is developing rapidly creates many innovations, one of which is used as a means of trade or e-commerce. Potme Farm is a business selling plant seeds, plants, and garden tools with a transaction process carried out manually, through social media or buyers come directly to the store. In this study, to create a website that suits user needs, potme farm website design uses the Design Thinking method with several stages, namely Empathize, Define, Ideate, Prototype, and Test which focuses on what is seen, felt, needed by users. The test results by testing each feature of the Potme Farm website using Maze Design obtained an overall result of 95% The value was obtained based on the average values that have been described from the key performance indicator including user success, average scenario processing time, and click errors by users. Based on the results of stages ranging from design, development, as well as testing and development of the Potme Farm website design with the Design Thinking method, it can produce a User Interface (UI) design that suits user needs (User Experience).